Motivational Interviewing and Glycemic Control in Adolescents With Poorly Controlled Type 1 Diabetes: A Randomized Controlled Pilot Trial - Tuomaala, Anna-Kaisa; Hero, Matti; Tuomisto, Martti T.; Lähteenmäki, Maria; Miettinen, Päivi J.; Laine, Tiina; Wehkalampi, Karoliina; Kiiveri, Sanne; Ahonen, Pekka; Ojaniemi, Marja; Kaunisto, Kari; Tossavainen, Päivi; et al. (Frontiers in Endocrinology, 2021)
Objective: To investigate whether motivational interviewing (MI), used by diabetes physicians, improves glycemic control and variability in the follow-up of poorly controlled adolescent patients with type 1 diabetes. Research design and methods: In this multicenter, randomized controlled trial, adolescent type 1 diabetes patients (n = 47), aged 12 to 15.9 years, with poor glycemic control (HbA1c >75 mmol/mol/9.0%) were randomized to standard education (SE) only or MI + SE. Study physicians were randomized to employ MI + SE (N = 24 patients) or SE only (N = 23). The patients were followed up every three months for a period of 12 months, and the main outcome measures were assessed at each visit (HbA1c) or 6-monthly (time in range [TIR] and glycemic variability [CV]). Results: The mean adjusted 12-month changes in HbA1c were similar in the MI + SE and SE only groups (-3.6 vs. -1.0 mmol/mol). Similarly, no differences in mean adjusted 12-month changes in TIR (-0.8 vs. 2.6 %, P = 0.53) and CV (-0.5 vs. -6.2, P = 0.26) were found between the groups. The order of entering the study correlated significantly with the 12-month change in HbA1C in MI + SE group (r = -0.5, P = 0.006) but not in SE only group (r = 0.2, P = 0.4). MI was not related to changes in quality of life. Conclusions: Short-term use of MI by diabetes physicians in managing adolescents with poorly controlled type 1 diabetes was not superior to SE alone. However, improving skills in applying the MI method in the outpatient clinic may be associated with more benefit in glycemic control.